Exploitation of heterosis for growth, flower quality and yield traits in China aster (Callistephus chinensis) - KUMARI, PRATIKSHA; KUMAR, RAJIV; RAO, T MANJANATHA; BHARATHI, T USHA; DHANANJAYA, M V; BHARGAV, V (The Indian Journal of Agricultural Sciences, 2023)
A line × tester set of 8 parents involving five females (Arka Kamini, Arka Poornima, Arka Aadya, Arka Archana, Arka Violet Cushion) and three pollen parents (Arka Shashank, Local Violet, Local Pink) were analyzed for heterosis with respect to growth, flower quality and yield traits in China aster [Callistephus chinensis (L.) Nees]. The experiments were conducted at Division of Floriculture and Medicinal Crops, ICAR-Indian Institute of Horticultural Research, Bengaluru during 2015-17. Results revealed that the cross L2 × T1 exhibited highest positive significant heterosis for plant height over mid parent, better parent as well as commercial check cv. Arka Kamini. For days to first flowering, cross L3 × T1 exhibited maximum negative heterosis over commercial check. The cross L2 × T1 exhibited highest positive significant heterosis for duration of flowering over mid parent, better parent as well as commercial check. For flower stalk length, the highest positive significant heterosis over mid parent, better parent as well as commercial check was observed in cross L4 × T3. The cross L3 × T2 recorded highest heterosis for flower yield over better, mid and commercial check.